Meaning Visualization: A Saussurean Semiotic Analysis of the Film Merry Riana - Ramadhani, Zahra Shafa; Musa, Purnawarman; Pertiwi, Cholidah Astri (COMMUSTY Journal of Communication Studies and Society, 2023)
The objective of this study is to determine the motivational messages that are sent in the movie "Merry Riana: Million Dollar Dream" to identify the inspirational messages. The semiotic theory developed by Ferdinand de Saussure is used in this study. Through the use of this theoretical method, the meaning of signified and signifiers that are present in the movie Merry Riana is investigated. Identification of signified and signifier aspects in the film Merry Riana is carried out through variations of scenes that appear in the film. Apart from that, the method used is a qualitative approach by collecting data through observation and interviews with several sources who have insight into the film or were inspired by the film Merry Riana. The informants who conducted this interview included general audiences, film academics, and the film community, totaling nine informants. The result of the research finds that the film Merry Riana can inspire its viewers, and there are many inspirational messages for the audience in the film Merry Riana.